The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4172/2155-9600.1000647
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Some Essential Oils on the Quality Aspect and Shelf Life of Meat

Abstract: Plant essential oils (EOs) serve as a «safe» alternative to chemical or synthetic antimicrobials and antioxidants to struggle with the food borne pathogens or spoilage organisms, inhibiting lipid oxidation and thus extend shelf life of ground beef application. In our study, we investigated the effectiveness of thyme oil (Thymus vulgaris) at concentrations (1%, 1.5% and 2%) and cinnamon oil (Cinnamomum zeylanicum) at concentrations (0.5%, 1% and 1.5%) as natural preservatives as well as their ability to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
(61 reference statements)
2
4
0
Order By: Relevance
“…So, the studied EOs bettered the microbial quality of beef sausage relative to the control formula. This result agrees with what is reported by El Adab & Hassouna, and Shaltout et al [31,6]. This decrease in the TBC values proved that thyme EO or clove EO has antimicrobial activities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…So, the studied EOs bettered the microbial quality of beef sausage relative to the control formula. This result agrees with what is reported by El Adab & Hassouna, and Shaltout et al [31,6]. This decrease in the TBC values proved that thyme EO or clove EO has antimicrobial activities.…”
Section: Discussionsupporting
confidence: 93%
“…This test goals to find EOs that act as a "safe" substitute for artificial antioxidants and synthetic antimicrobials. Hence, nowadays, research is directed to detect EOs that can prevent the growth of both harmful and pathogenic organisms and inhibit fat oxidation for prolonging the shelf life of the food products [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the antimicrobial effect of chitosan significantly (p < .05) decreased the TVBN concentration of T 3 as compared to T 1 and T 2 . A similar increasing trend in TVBN was also observed in minced meat treated with thyme and cinnamon essential oil (Shaltout, Thabet, & Koura, 2017). The results in the present study also corroborated with the reduction in microbial load, TBARS and TVBN value in fish patties coated with sunflower protein films incorporated with clove essential oil than control during refrigerated storage for 13 days as reported by Salgado, Lopez-Caballero, Gomez-Guillen, Mauri, and Montero (2013).…”
Section: Total Volatile Basic Nitrogen (Tvbn)supporting
confidence: 91%
“…Furthermore, the obtained results indicated that the best acceptability quality was attained at mixed group (thyme oil 0.4% +cinnamon oil 0.4%) then in thyme oil-treated minced beef samples, while slight improvement in acceptability of cinnamon oil minced beef samples as compared with control samples These results agreed with those obtained by Sasse et al, (2009) who reported that many herbs and spices as thyme contain antioxidant components that improve both color and flavor stability in meat. Also, Sallem-Amany et al, (2010) indicated that sensory properties of minced beef samples during cold storage (4°C)were enhanced by treatment minced beef by different concentrations of thyme oil (0.5%, 1%, 1.5%) compared to the untreated (control) samples and sample contain 1.5% thyme oil revealed best enhancement of sensory properties than sample contain 0.5% of the same oil, and those obtained by Shaltout et al,(2017) whose results were that meat samples containing 2% thyme oil and 1.5% cinnamon oil, demonstrated the highest enhancement of sensory attributes, while the samples treated with 1% of thyme and 0.5% of cinnamon oils demonstrated lower enhancement.…”
Section: Discussionmentioning
confidence: 99%